Follicular CD8+ T Cells: Origin, Function and Importance during HIV Infection - Perdomo-Celis, Federico; Taborda, Natalia Andrea; Rugeles, María Teresa (Frontiers in Immunology, 2017)
The lymphoid follicle is critical for the development of humoral immune responses. Cell circulation to this site is highly regulated by the differential expression of chemokine receptors. This feature contributes to the establishment of viral reservoirs in lymphoid follicles and the development of some types of malignancies that are able to evade immune surveillance, especially conventional CD8+ T cells. Interestingly, a subtype of CD8+ T cells located within the lymphoid follicle (follicular CD8+ T cells) was recently described; these cells have been proposed to play an important role in viral and tumor control, as well as to modulate humoral and T follicular helper cell responses. In this review we summarize the knowledge on this novel CD8+ T cell population, its origin, function and potential role in health and disease, in particular, in the context of the infection by the human immunodeficiency virus.